Comparison of psychological stress, depression and anxiety among medical and engineering students - Chenganakkattil, Shabeer; K., Jibin Babu; Hyder, Shafeen (International Journal of Research in Medical Sciences, 2017)
Background: Medical students encounter multiple emotions in transformation from insecure students to young knowledgeable physicians, leading to a growing concern about psychological distress in medical training. Torturous admission protocols, portions beyond horizons, new skills to be mastered, expectations of family members, competition and the uncertainty involved about the future comprise a few among the background stressors. The objective was to study stress, depression and anxiety in medical students in comparison with engineering students. Methods: A cross-sectional study was conducted comparing perceived stress, depression and anxiety among 150 medical and 150 engineering students selected through randomized sampling. Perceived Stress Scale, Zung depression and Zung anxiety scales were administered to the selected students. Results: Seventy-two percentage of medical students perceived moderate and high levels of stress compared to 56.7% of engineering students in this study. Overall prevalence of depression was higher among medical students (20.6%) compared to engineering students (15.3%). Anxiety was also higher among medical students (19.4%) compared to engineering students (11.3%). Conclusions: Medical students perceived more stress when compared to engineering students. Rates of depression and anxiety were also higher among them. Stress interventional strategies need to be designed to improve the psychological wellbeing of the students and consequently improve the doctor patient relationship. This study suggests to promote stress management modalities early in the medical career.